Acesso minimamente invasivo da artéria renal com diferentes tipos de cateteres mediante radiologia convencional - Cunha, João Paulo Monteiro Carvalho Mori da (2011)
Acute and Chronic renal diseases have a high morbidity and mortality. There is a good deal of interest in MSC-based approaches for the treatment of Kidney injury, thanks to positive preclinical results and the strong clinical need for novel therapies to treat Acute Kidney Injury. Several routes of administration have been tested and have shown a better response when applied arterially. The main goal of this study was to describe and to compare the use of Fogarty thru-lumen embolectomy catheter with angiographic catheter by using conventional radiology as a guide. We used seven healthy dogs to measure the diameter of the aorta caudal to the renal arteries and right and left femoral and renal arteries. It was assessed the number of attempts for the placement of the introducer, number of radiographic studies to carry out nefrography with both cathethers. In five out of seven animals it was possible to place of the introducer tube 6F. Regarding the number of radiographic films used, the technique with the angiographic catheter needed more than the Fogarty when accessed both arteries, but there is no significant difference when compared to the Fogarty with access to only one renal artery. There was hematoma formation in three animals. The access of the renal artery for drug delivery and cell therapy is possible using both Fogarty thru-lumen embolectomy catheter and angiographic catheter by conventional radiology as a guide, however, we considered the Fogarty catheter easier to be applied, since only one procedure can be performed to access both renal arteries, thus making it less expensive and faster to run. If access to only one renal artery is require, the angiographic catheter would be recommended, since cell therapy would be administered more selectively in the target kidney.